Teachers' understanding of mainstreaming learners with autism disorders at rural primary schools - Ngidi, Thembile (University of the Free State, 2024)
This study explores teachers' understanding of mainstreaming learners with autism in rural primary schools in KwaZulu-Natal, South Africa, focusing on the specific challenges and support systems in under-resourced settings. Employing a qualitative, phenomenological approach, the study draws on an alternative theoretical framework more suited to the research context, replacing the previously applied Cultural-Historical Activity Theory (CHAT). Data were gathered through semi-structured interviews and document analysis, capturing insights from teachers in rural areas regarding their knowledge, perceptions, and experiences of inclusive education. The study involved a purposive sample of teachers in rural primary schools, with considerations for their gender, age, qualifications, teaching experience, and cultural background. Findings reveal that while teachers generally express positive attitudes toward inclusion, they face substantial challenges, including a lack of autism-specific training, inadequate professional support, and insufficient access to specialists and educational resources. Cultural misconceptions about autism further contribute to difficulties in mainstreaming learners effectively. The study recommends targeted professional development programs, increased funding for inclusive education in rural schools, and stronger community engagement initiatives to raise awareness and reduce stigma surrounding autism. By emphasizing the crucial role of teachers in inclusive education, this research provides practical insights for policymakers and educators to enhance the mainstreaming of learners with autism in South African rural schools.
Thesis (D.Ed. (Educational Psychology))--University of the Free State, 2024